Plasma leptin and exercise: recent findings - Hickey, M. S.; Calsbeek, D. J. (Sports Medicine, 2001)
The cloning of murine and human obese genes in 1994, and the subsequent identification that the product of the obese gene, leptin, is secreted from adipose tissue, stimulated a tremendous amount of interdisciplinary interest in adipose tissue endocrinology and the potential role of this tissue in the regulation of energy balance. Exercise, with concomitant changes in fuel flux, systemic hormone levels and energy expenditure, may contribute to the regulation of plasma leptin levels and presumably, leptin action. The initial work characterising the leptin-exercise relationship was equivocal. Cross-sectional studies provided some mixed evidence regarding the relationship between aerobic capacity or habitual physical activity and plasma leptin. In contrast, studies on acute bouts of exercise and exercise training interventions have, with few exceptions, suggested that exercise does not alter systemic leptin independent of changes in fat mass. In general, these studies did not carefully control for energy balance, and sampled only a single fasting plasma leptin level. Two recent studies utilising experimental designs in which energy balance was controlled and 24-hour profiles of plasma leptin were determined have provided the most compelling evidence to date of the interaction between exercise, energy balance and systemic leptin in humans. These studies provide a clear explanation for the apparent lack of an acute effect of exercise on systemic leptin and underscore the importance of clearly defining the balance between energy intake and energy expenditure when studying the physiology of leptin. The aim of this brief review is to provide an overview of the interaction between energy expenditure during physical activity and systemic leptin level. Special emphasis will be placed on those studies in which energy intake/balance was carefully controlled.